Grand challenges in metamaterial antennas - Virdee, Bal Singh (Frontiers, 2022)
Future wireless technologies necessitate the development of next generation subsystems of antennas that are highly efficient and capable of simultaneously supporting multiple functions for the transmission and reception of RF signals over a wide frequency band. Reduction in antenna size has become a critical factor in the miniaturization of wireless communication systems. The challenge for researchers in academia and industry is to develop innovative solutions by exploiting the novel characteristics exhibited by 2D and 3D metamaterials. Discussed in the paper the need for electrically small antennas, antenna gain, and isolation enhancement based on metamaterial principles. It is also noted that wireless power transfer technologies incorporating the metamaterial can offer an enhanced transmission performance.